Answered

Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

9t-6-6t=6. How do you find the answer

Sagot :

I'm guessing the question is to solve for t.
you reduce the terms, move all of the t's to one side, and move everything else to the other side, then divide by the coefficient of t.
9t-6-6t=6
3t-6=6
3t=12
t=4
[tex]9t-6-6t=6\\ 3t=12\\ t=4[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.